Which psychological needs profile exhibits higher engagement and favorable attitudes toward interprofessional education? A cluster analysis among health and social care Hong Kong students - John Ian Wilzon T. Dizon; Qing He; Xiaoai Shen; Pauline Luk; Doris Yin Kei Chong; Karen Man Kei Chan; Chad Wing Nga Chan; Sarah So Ching Chan; Jacky Chak Pui Choy; Chor Yin Lam; Diana Pui Ling Lee; Michael Magtoto Manio; et al. (BMC Medical Education)
Abstract Background This study aimed to investigate which basic psychological needs profile, based on different levels of autonomy, competence, and relatedness, could exhibit higher student engagement and favorable attitudes toward interprofessional education (IPE). Methods A total of 341 undergraduate and postgraduate health and social care students enrolled in an IPE simulation participated in this study. Data were analyzed using a person-centered approach using a two-step cluster analysis, multiple analysis of variance, and bootstrapped independent t-tests. The participants completed the self-report scales such as the basic psychological needs in general questionnaire, interprofessional attitudes scale, and engagement versus disaffection with learning scale. Results Two basic psychological needs profiles emerged from the cluster analysis: a high basic psychological needs profile (i.e., high autonomy, moderately high competence, and very high relatedness) and a low basic psychological needs profile (i.e., low autonomy, moderately low competence, and very low relatedness). Students with high basic psychological needs profiles (n = 140; 41%) had more positive attitudes about IPE and were more behaviorally and emotionally engaged in participating in IPE tasks than students with low basic psychological needs profiles (n = 201; 59%). Conclusions Findings suggest that health and social care students’ engagement and attitudes toward interprofessional education differed based on their basic psychological needs profiles. Health professions educators can leverage students’ basic psychological needs in designing interventions and simulation activities to promote students’ engagement and collaborative outcomes in IPE. Enhancing students’ basic psychological needs could be crucial in fostering greater behavioral and emotional engagement and positive attitudes in participating in IPE.